2015
DOI: 10.1073/pnas.1422313112
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive method for detecting ubiquitinated substrates using TR-TUBE

Abstract: The identification of substrates for ubiquitin ligases has remained challenging, because most substrates are either immediately degraded by the proteasome or processed by deubiquitinating enzymes (DUBs) to remove polyubiquitin. Although a methodology that enables detection of ubiquitinated proteins using ubiquitin Lys-e-Gly-Gly (diGly) remnant antibodies and MS has been developed, it is still insufficient for identification and characterization of the ubiquitin-modified proteome in cells overexpressing a parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 36 publications
2
92
0
Order By: Relevance
“…We analyzed proteins ubiquitinated upon lysosomal damage by using the trypsin-resistant tandem ubiquitin-binding entity (TR-TUBE) method, which we recently developed, to identify ubiquitin ligase substrates (18), and found that SCF FBXO27 ubiquitinates luminal sites on the lysosomal protein LAMP2.…”
Section: Significancementioning
confidence: 99%
“…We analyzed proteins ubiquitinated upon lysosomal damage by using the trypsin-resistant tandem ubiquitin-binding entity (TR-TUBE) method, which we recently developed, to identify ubiquitin ligase substrates (18), and found that SCF FBXO27 ubiquitinates luminal sites on the lysosomal protein LAMP2.…”
Section: Significancementioning
confidence: 99%
“…After tryptic digest another level of enrichment was achieved by using a-GlyGly-Lys antibodies to pull-out ubiquitinated peptides, which were identified by MS. This identified eight ubiquitination sites in substrates of Skp2 and another six in substrates of FBXO21 [114].…”
Section: Tandem Ubiquitin Binding Entity (Tube) Based Enrichmentmentioning
confidence: 97%
“…By combining several UBA domains in one TUBE the specificity of the chain-enrichment can be modulated [112,113]. The technique has been applied to study specific E3 ligase substrates in vivo by overexpressing them together with a FLAG-tagged, trypsin-resistant TUBE (TR-TUBE) [114]. An interesting alternative for monitoring ubiquitin chains in vivo has Probing the ubiquitin landscape been developed by combining the TUBE-probe with fluorescent probes, allowing imaging of ubiquitin chains in certain parts of the cell [115].…”
Section: Tandem Ubiquitin Binding Entity (Tube) Based Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Including a GST-tag on the TUBEs allows conventional affinity purification with glutathione-coupled beads. Therefore, TUBEs have been used as 'ubiquitin-traps' to isolate endogenous ubiquitylated proteins from different biological sources such as cell lines, tissues, organs [15] or to study global ubiquitylation events by mass spectrometry [16][17][18][19][20][21]. Besides the enrichment of ubiquitylated proteins on a large scale, the TUBEs affinity purification can also isolate ubiquitin-interacting partners that regulate and/ or connect with distinct functions [17,20,21].…”
mentioning
confidence: 99%